Comparison of the 2024 Presidential and Vice-Presidential Candidates using Social Media - Revolusi, Prabu (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This research underlines the relevance of communication strategies in gathering votes in politics, especially in the modern political era which is characterized by the vital role of social media in spreading political messages and influencing public opinion. The focus on the use of social media in determining the choice of 2024 presidential and vice presidential candidates, especially Prabowo Subianto and Gibran Rakabuming Raka, shows awareness of the importance of access to information that is easy to understand and relevant for each individual. The importance of further research to understand the information more deeply highlights awareness of the importance of criticism in consuming social media content. Apart from being a source of information, social media is also seen as a channel for people's aspirations and views, turning it into a participatory tool in the political process. Thus, this research shows that social media has a significant role in the process of determining political choices, especially in the context of the 2024 presidential election. Understanding the comparison of social media in political communication is an important key for prospective leaders to be able to respond effectively to the aspirations and needs of the community.